Association between oxidative balance score and gallstone disease: a population-based study from NHANES - Zhang, Mengmeng; Yang, Aiming (Frontiers in Nutrition, 2025)
BackgroundOxidative stress has been reported to participant in the pathogenesis of gallstones. Oxidative balance score (OBS) represents pro-oxidant and antioxidant exposures to diet and lifestyle, closely associated with multiple metabolic disorders. However, the relationship between OBS and gallstones remains unclear.MethodsThis study analyzed cross-sectional data from the National Health and Nutrition Examination Survey (NHANES) 2017–2020. OBS was calculated based on the 24-h recall interviews or questionnaires. We used weighted logistic regression, restricted cubic splines (RCS), weighted quantile sum (WQS) regression and the Bayesian kernel machine regression (BKMR) model to identify the relationship between OBS and gallstones. Subgroup analysis and sensitivity analysis were used to explore potential heterogeneity and stability of the results. Mediation analysis was performed to assess the mediating effects of serum lipid in the association between OBS and gallstones.ResultsA total of 7,618 participants were finally included in this study. Weighted logistics regression showed that total OBS was associated with gallstones risk (OR = 0.98, p = 0.03), particularly in individuals who were under 60 years old, Hispanic, educated below high school, non-smokers, had hypertension or malignancy. Dietary and lifestyle OBS independently contribute to the protection against gallstones. RCS analysis indicated a non-linear relationship between OBS and gallstones (p = 0.03). WQS and BKMR model identified that BMI, vitamin E, vitamin B6, magnesium and carotene played relatively important role among 20 components. Mediation analysis showed serum TG and HDL as mediators of the association between OBS and gallstones.ConclusionHigher OBS or increased oxidative balance are positively associated with reduction of gallstone risk. This findings provide valuable insights for surveillance and interventions targeting for antioxidant-rich diet and lifestyle for gallstone disease.